2013
DOI: 10.2337/dc12-2148
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Mortality of New-Onset Diabetes After Dialysis

Abstract: OBJECTIVEWe examined the predictors and risks associated with pre-existing versus new-onset diabetes mellitus (DM) after initiation of chronic dialysis therapy in end-stage renal disease (ESRD) patients.RESEARCH DESIGN AND METHODSIn the Taiwan National Health Insurance Research Database, we examined records of ESRD patients who initiated dialysis between 1999 and 2005. Patients were followed until death, transplant, dialysis withdrawal, or 31 December 2008. Predictors of new-onset DM and mortality were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 29 publications
6
64
0
Order By: Relevance
“…Since new-onset diabetes and IGT (NODI) is a common complication among patients on dialysis (4)(5)(6)8), it is important to explore the potential risk factors for this complication. However, published data on this issue are limited in dialysis populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since new-onset diabetes and IGT (NODI) is a common complication among patients on dialysis (4)(5)(6)8), it is important to explore the potential risk factors for this complication. However, published data on this issue are limited in dialysis populations.…”
mentioning
confidence: 99%
“…A previous study has indicated the potential side effects of dialysate glucose including a tendency for hyperglycemia and hyperinsulinemia in a dose-dependent manner in PD patients (14). However, 2 recent papers did not compare the higher risk for new-onset diabetes in PD populations with their hemodialysis (HD) counterpart (6,7). It is therefore of interest to explore the potential effect of the amount of dietary energy intake and glucose absorption via dialysate on the incidence of NODI in PD patients.…”
mentioning
confidence: 99%
“…Several studies have reported that NODM occurs among patients receiving dialysis at rates greater than in the general population [7][8][9] . According to the Centre for Disease Control's web page 11 , the incidence rate for DM in the general population in the US fluctuated around 0.5%-0.9% per year from 2000 to 2009.…”
Section: Epidemiology Of New-onset Diabetes Mellitus After Dialysismentioning
confidence: 99%
“…In recent years, new-onset diabetes mellitus (NODM) after the initiation of dialysis has been reported in several studies [7][8][9][10] . This critical review focuses on the epidemiology and risk factors of NODM after dialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, for patients undergoing PD, obligatory carbohydrate absorption with PD solutions has been considered to be an additional potential risk. However, 2 recent studies from Taiwan have compared the risk of new-onset diabetes mellitus among incident hemodialysis and PD patients and have found either an equivalent or lower risk among patients starting PD (13,14). Beyond this comparison with hemodialysis, however, there remains a substantial gap in understanding regarding risk factors and predictors of new-onset diabetes for patients initiating PD therapy.…”
mentioning
confidence: 99%